(untitled) (Jurnal Inovasi Pendidikan Kimia, 2024)
Redox and electrochemistry are materials that students consider difficult. One of the difficulties experienced by students is in balancing redox reactions using the oxidation number method. This condition is exacerbated by learning activities that must be carried out from home, resulting in low student motivation and learning outcomes. Therefore, innovative learning methods are needed but are still effective if applied online. One learning model that can be applied is STEM-PjBL, which is based on blended learning. The research aims to determine the differences in motivation and learning outcomes of students who are taught using the STEM-PjBL learning model based on blended learning and the lecture learning model. This research is quasi-experimental and uses a post-test-only control design research design. The research population was students of class XII Science at SMAN 5 Malang in the 2021/2022 academic year. The sample was class XII G and H, totaling 63 people by purposive sampling. The data collected include student learning outcomes, cognitive, affective, and psychomotor aspects, and student motivation questionnaires. The research results show differences in learning outcomes and motivation between students who apply the STEM-PjBL learning model and those who apply conventional learning. Student responses to using STEM-PjBL-based learning models and media were 41% very happy, 50% liked it, and 9% quite good.